Advances in surface‐enhanced Raman scattering bioprobes for cancer imaging. Issue 4 (18th March 2021) - Lin, Jie; Akakuru, Ozioma Udochukwu; Wu, Aiguo
Abstract: Surface‐enhanced Raman scattering (SERS) technology with feature of high sensitivity, selective enhancement, in situ detection, nondestructive, label free, and fingerprint spectrum has been widely utilized in various practical applications, especially for bioanalysis. Cancer diagnosis and therapy based on SERS bioimaging has been reported as a promising approach in recent decades, and various types of material‐based SERS bioprobes are rapidly designed continuously. SERS bioimaging has been successfully employed in cancer screening, diagnosis, and componential analysis in both in vitro and in vivo cancer tissue samples, which simultaneously provides visual morphology and biochemical information. Precise tumor tissue excision, real‐time monitoring of cellular uptake process, and noninvasive cell tracking and labeling are realized due to the effective Raman image bioprobes, satisfying the requirements of precision medicine. Here, an overview of SERS bioprobes based on noble metals, metal oxides, and composite materials is presented by highlighting their respective, unique advantages and recent achievements in cancer imaging realm. This review also offers a distinctive perspective on designing multifunctional micro–nanoparticles with remarkable SERS activity, and proposing novel strategies for establishing high‐performance sensors and imaging bioprobes derived from the deep insight of enhancement mechanism for different types of SERS substrates. Abstract : SERS bioimaging has been successfully employed in cancer screening, diagnosis, and componential analysis in both in vitro and in vivo cancer tissue samples, which simultaneously provides visual morphology and biochemical information. Precise tumor tissue excision, real‐time monitoring of cellular uptake process, and noninvasive cell tracking and labeling are realized due to the effective Raman image bioprobes, satisfying the requirements of precision medicine.